Critical Factors in the Implementation of Risk Awareness Education in Universities in China - Liu, Ling; Pei, Xiaoge; Han, Yingchun; Liao, Xiaoling (Frontiers in Psychology, 2022)
Under the influence of social changes, latent factors in campus safety are increasing, and dealing with them is becoming more difficult. Facing the challenges in the pluralistic society, students need to cope with the changes of external and internal environments in the dynamic society. Additionally, there are new events on campus at any time, which may lead to campus risk. The frequent events that have occurred on campus in recent years have created difficulties for school administrative units. Implementing campus risk management strategies and conducting risk awareness education campaigns are, therefore, necessary. The fact that we are in a technologically dynamic age is another factor that makes risk awareness and proper risk management essential for individual survival and sustainable development of organizations. The participants of the study were university students in Nanchang, Jiangxi Province. Three hundred copies of the questionnaire were distributed, and 238 valid copies were retrieved, representing a retrieval rate of 79%. The results of the survey show that “life education” is the most emphasized dimension, followed by “curriculum and instruction,” and “environmental planning.” The five most emphasized indicators among the 14 indicators are opportunity education, physical activity, role-play, team competition, and learning area planning. The results suggest that school administrative units can take control in an emergency and reduce the likelihood of school members being threatened or harmed by the risk factor, and educators can make a quick decision to turn risk into opportunity.